Analisis Biaya Distribusi Semen Menggunakan Metode Distribution Requirement Planning (DRP) di PT XYZ - Winata, Putu Adi; Utami, Ni Made Cyntia; Setiawati, Ni Luh Putu Lilis Sinta (Study Program of Industrial Engineering, Udayana University, 2025)
The construction industry and infrastructure development are crucial aspects of a country's economic advancement, with cement being a key primary material. Cement consumption in Indonesia has shown steady growth, reaching 65.2 million tons in 2021, an increase of 4.3% from the previous year. PT XYZ, a cement distributor, plays a vital role in ensuring the supply of cement in the regions of Bali, NTB, NTT, and East Kalimantan. However, the current distribution process is not optimal as deliveries are made solely based on customer demand, leading to stock shortages and high shipping costs. To address these issues, distribution will be planned and scheduled using the Distribution Requirements Planning (DRP) method. With effective scheduling and planning, customer demand will be met more efficiently, and sales performance will improve as demand is fulfilled promptly and in the right quantities. Consequently, distribution costs can be minimized. The results of the study indicate that the implementation of DRP has significantly improved distribution efficiency. Cement distribution has become organized and scheduled on a monthly basis, ensuring optimal product availability with more efficient shipping costs. Before the implementation of DRP, distribution costs totaled IDR 134,697,600,000, and this amount decreased to IDR 115,190,064,000 after the application of DRP, reflecting a cost savings of IDR 19,507,536,000, or 14%. Thus, the application of DRP has enabled the optimization of inventory management, enhanced operational efficiency, and significantly reduced distribution costs.